Escrita teclada x escrita padrão na produção textual: a experiência de adolescentes brasileiros - Ana Lucia Gomes; Jane Correa (Universidade do Minho, 2009)
The computer connected to the internet has been promoting great changes in written language. As a result of the use of instant communication devices, new text genres have been emerged along with specific linguistic features in writing, which make communication through digital texts more dynamic and functional. The present work discusses teenagers' use of written language on the internet as related to digital text genres in the context of an electronic culture. It is argued that the specific linguistic features of the written language on the internet would not be transposed to other discursive contexts unless implicit or explicitly acknowledged. This suggests that linguistic choices made by teenagers are sensitively related to the discursive contexts.